Age-related insult of cochlear ribbon synapses: An early-onset contributor to D-galactose-induced aging in mice. (February 2020) - Du, Zheng-De; Han, Shu-Guang; Qu, Teng-Fei; Guo, Bin; Yu, Shu-Kui; Wei, Wei; Feng, Shuai; Liu, Ke; Gong, Shu-Sheng
Abstract: Presbycusis results from age-related degeneration of the auditory system. D-galactose (D-gal)-induced aging is an ideal and commonly used animal model in aging research. Previous studies demonstrate that administration of D-gal can activate mitochondria-dependent apoptosis in the cochlear stria vascularis. However, D-gal-induced changes to cochlear inner (IHCs) and outer (OHCs) hair cells, spiral ganglion cells (SGCs), and ribbon synapses connecting IHCs and SGCs have not been systematically reported. The current study investigated changes in the numbers of hair cells, SGCs, and ribbon synapses in the mouse model of aging. We found that in comparison to control mice, the numbers of ribbon synapses and their nerve fibers were significantly decreased in D-gal-treated mice, whereas the numbers of OHCs, IHCs, and SGCs were almost unchanged. Moreover, hair cell stereocilia were also not obviously influenced by D-gal administration. Although D-gal-induced aging did not significantly shift the auditory brainstem response (ABR) thresholds in the 8, 16, and 32 kHz frequency bands, the amplitude and latency of the ABR wave I, reflecting ribbon synapse functions, were abnormal in D-gal-treated mice compared to control mice. We also found that 8-hydroxy-2-deoxyguanosine, a marker of oxidative DNA damage, was significantly increased in mitochondria of cochleae from mice exposed to D-gal-induced aging in comparison to control mice. Moreover, D-gal administration increased the levels of H2 O2 and mitochondrial 3860-bp common deletion, and decreased superoxide dismutase activity and ATP production in the cochlea. Furthermore, compared with control mice, the protein levels of NADPH oxidase 2 and uncoupling protein 2 were significantly increased in the cochlea of D-gal-treated mice. Taken together, these findings support that the cochlear ribbon synapse is the primary insult site in the early stage of presbycusis, and mitochondrial oxidative damage and subsequent dysfunctions might be responsible for this insult. Highlights: Ribbon synapse is the primary insult site in the cochlea of D-galactose-induced aging mice. ROS-induced mitochondrial DNA damage in cochlear IHCs and SGCs might be partly responsible for this insult. NADPH oxidase might be an important source of ROS in the cochlea.